Two new species of Batriscenellus Jeannel from tropical Asia (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Kleeberg, Andreas (Zootaxa, 2020)
The genus Batriscenellus Jeannel is recorded from Southeast Asia for the first time, with two species described as new: B. suthepensis Yin & Kleeberg, sp. nov. from Chiang Mai, Thailand, and B. vietnamicus Yin & Kleeberg, sp. nov. from Vinh Phuc, Vietnam. The male of both new species can be readily separated from those of all congeners by the unique shape of the modification on tergites 1 (IV), as well as the structure of the aedeagus.